Association Between Cumulative Exposure to Increased Low-Density Lipoprotein Cholesterol and the Prevalence of Asymptomatic Intracranial Atherosclerotic Stenosis - Kang, Kaijiang; Wang, Yu; Wu, Jianwei; Wang, Anxin; Zhang, Jia; Xu, Jie; Ju, Yi; Zhao, Xingquan (Frontiers in Neurology, 2020)
Background and Purpose: Intracranial atherosclerosis has gained increasing attention due to the high risk of recurrent clinical or subclinical ischemic events, while the relationship between low-density lipoprotein cholesterol (LDL-C) measured at a single time point and intracranial atherosclerotic stenosis (ICAS) is inconsistent. This study aims to assess the association between cumulative exposure to increased LDL-C and the prevalence of asymptomatic ICAS. Methods: The Asymptomatic Polyvascular Abnormalities Community study was investigated on the epidemiology of asymptomatic polyvascular abnormalities in Chinese adults. In this study, we included 4,523 participants with LDL-C measured at 3 examinations in 2006, 2008, and 2010. Cumulative exposure to increased LDL-C was calculated as following: LDL-C burden2006−2008 = [(LDL-C2006-1.8) + (LDL-C2008-1.8)]/2 * time2006−2008; LDL-C burden = LDL-C burden2006−2008 + LDL-C burden2008−2010. Transcranial doppler ultrasonography was performed in 2010 to detecting the ICAS. Results: Of the 4,347 patients, 13.3% (580/4,347) were diagnosed with ICAS. In univariate analysis, the association between LDL-C burden and ICAS prevalence was significant, the odds ratios (95% confidence interval) from the lowest to the highest quartile were 1 (reference), 1.30 (0.99–1.70), 1.32 (1.01–1.73), and 2.14 (1.66–2.75), respectively (P < 0.05). After adjustment for potential confounding factors, the same result was reached. Conclusions: Cumulative exposure to increased LDL-C is concentration-dependently associated with increased prevalence of asymptomatic ICAS, especially in those under the age of 65 y or free of hypertension, diabetes mellitus, and hyperlipidemia.